Vocational specifications for junior pharmacists - Sulashvili, Nodar; Beglaryan, Margarita; Matoshvili, Maia (Caucasus Journal of Health Sciences and Public Health, 2018)
Aim and objects was to study peculiarities of junior pharmacists in Georgia. The study was quantitative investigation by using survey (Questionnaire). Surveys was for junior pharmacists, 314 junior pharmacist specialists were interviewed in Georgia. Questions and answers are given in the tables. On each question are attached diagram or table. Questionnaire and diagrams are numbered. On the question are you satisfied with your professional (occupational) choice? junior pharmacist specialist’ 82.2% were satisfied with professional choice, junior pharmacist specialist’ 9.6% were partly satisfied with professional choice , junior pharmacist specialist’ 3.5% have doubts with professional choice, junior pharmacist specialist’ 2.2% were disappointed with professional choice and junior pharmacist specialist’ 2.5% were not satisfied with professional choice. On the question are you satisfied with your job (work)? junior pharmacist specialist’ 34.4% answer yes, junior pharmacist specialist’ 34.1% answer partially, junior pharmacist specialist’ 30.9% answer no. And junior pharmacist specialist’ 0.6% answer cannot say. On the question how long do you need for mastering (assimilation) under the conditions of a new job position? Junior pharmacist specialists’ 3.5% answer up to 1 month, junior pharmacist specialists’ 33.1% answer up to 3 months, junior pharmacist specialists’ 44.9% answer up to 6 months, junior pharmacist specialists’ 14% answer up to 9 months, junior pharmacist specialists’ 4.1% answer up to 1 year, and junior pharmacist specialists’ 0.3% answer more than 1 year. On the question would you like to leave your profession? Junior pharmacist specialists’ 2.9% answer yes, junior pharmacist specialists’ 92% answer no, junior pharmacist specialists’ 5.1% answer I have thoughts. On the question would you like to leave your profession? Junior pharmacist specialists’ 2.9% answer yes, junior pharmacist specialists’ 92% answer no, junior pharmacist specialists’ 5.1% answer I have thoughts.